Application progress of plant-mediated RNAi in pest control - Li, Xiang; Liu, Xiaoguang; Lu, Wenhui; Yin, Xinming; An, Shiheng (Frontiers in Bioengineering and Biotechnology, 2022)
RNA interference (RNAi)-based biopesticides are novel biologic products, developed using RNAi principles. They are engineered to target genes of agricultural diseases, insects, and weeds, interfering with their target gene expression so as to hinder their growth and alleviate their damaging effects on crops. RNAi-based biopesticides are broadly classified into resistant plant-based plant-incorporated protectants (PIPs) and non-plant-incorporated protectants. PIP RNAi-based biopesticides are novel biopesticides that combine the advantages of RNAi and resistant transgenic crops. Such RNAi-based biopesticides are developed through nuclear or plastid transformation to breed resistant plants, i.e. dsRNA-expressing transgenic plants. The dsRNA of target genes is expressed in the plant cell, with pest and disease control being achieved through plant-target organism interactions. Here, we review the action mechanism and strategies of RNAi for pest management, the development of RNAi-based transgenic plant, and the current status and advantages of deploying these products for pest control, as well as the future research directions and problems in production and commercialization. Overall, this study aims to elucidate the current development status of RNAi-based biopesticides and provide guidelines for future research.